Functional organization of RNA polymerase II in nuclear subcompartments - Rippe, Karsten; Papantōnēs, Akēs (Current opinion in cell biology, 2022)
Distinct clusters of RNA polymerase II are responsible for gene transcription inside eukaryotic cell nuclei. Despite the functional implications of such subnuclear organization, the attributes of these clusters and the mechanisms underlying their formation remain only partially understood. Recently, the concept of proteins and RNA phase-separating into liquid-like droplets was proposed to drive the formation of transcriptionally-active subcompartments. Here, we attempt to reconcile previous with more recent findings, and discuss how the different ways of assembling the active RNA polymerase II transcriptional machinery relate to nuclear compartmentalization.
Part of special issue: SI: cell nucleus 2022
Gesehen am 19.08.2022